A Study about Schottky Barrier Height and Ideality Factor in Thin Film Transistors with Metal/Zinc Oxide Nanoparticles Structures Aiming Flexible Electronics Application - Kaufmann, Ivan Rodrigo; Zerey, Onur; Meyers, Thorsten; Reker, Julia; Vidor, Fábio; Hilleringmann, Ulrich (Nanomaterials)
Zinc oxide nanoparticles (ZnO NP) used for the channel region in inverted coplanar setup in Thin Film Transistors (TFT) were the focus of this study. The regions between the source electrode and the ZnO NP and the drain electrode were under investigation as they produce a Schottky barrier in metal-semiconductor interfaces. A more general Thermionic emission theory must be evaluated: one that considers both metal/semiconductor interfaces (MSM structures). Aluminum, gold, and nickel were used as metallization layers for source and drain electrodes. An organic-inorganic nanocomposite was used as a gate dielectric. The TFTs transfer and output characteristics curves were extracted, and a numerical computational program was used for fitting the data; hence information about Schottky Barrier Height (SBH) and ideality factors for each TFT could be estimated. The nickel metallization appears with the lowest SBH among the metals investigated. For this metal and for higher drain-to-source voltages, the SBH tended to converge to some value around 0.3 eV. The developed fitting method showed good fitting accuracy even when the metallization produced different SBH in each metal-semiconductor interface, as was the case for gold metallization. The Schottky effect is also present and was studied when the drain-to-source voltages and/or the gate voltage were increased.
Keywords: General Materials Science; General Chemical Engineering

Complementary Inverter Circuits on Flexible Substrates - Reker, Julia; Meyers, Thorsten; Vidor, Fabio F.; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Local Power Control using Wireless Sensor System for Microgrids in Africa - Hilleringmann, Ulrich; Petrov, Dmitry; Mwammenywa, Ibrahim; Kagarura, Geoffrey M. (2021 IEEE AFRICON)

The Viability of a Non-Flow Capacitive Biosensing Microsystem for Whole Cell Counting - Andrews, George; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (2021 IEEE AFRICON)

The Viability of a Non-Flow Capacitive Biosensing Microsystem for Whole Cell Counting - Andrews, George; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (2021 IEEE AFRICON)

Die berufliche Tabletaneignung von Lehrkräften als Beispiel der Mediatisierung pädagogischer Handlungskontexte. Theoretische Perspektiven und empirische Befunde - Gerhardts, Lara; Dehmel, Lukas; Meister, Dorothee M. (Jahrbuch Medienpädagogik 16. Medienpädagogik in Zeiten einer tiefgreifenden Mediatisierung)

Zur Entgrenzung der Arbeit des medienpädagogischen Weiterbildungspersonals im Kontext tiefgreifender Mediatisierung - Dehmel, Lukas (Erwachsenenpädagogische Digitalisierungsforschung. Impulse - Befunde - Perspektiven. Bielefeld)

Epistemologies of predictive policing: Mathematical social science, social physics and machine learning - Hälterlein, Jens (Big Data & Society)

Spanning the isogeny class of a power of an elliptic curve - Kirschmer, Markus; Narbonne, Fabien; Ritzenthaler, Christophe; Robert, Damien (Mathematics of Computation)
Let E be an ordinary elliptic curve over a finite field and g be a positive integer. Under some technical assumptions, we give an algorithm to span the isomorphism classes of principally polarized abelian varieties in the isogeny class of E⁹ . The varieties are first described as hermitian lattices over (not necessarily maximal) quadratic orders and then geometrically in terms of their algebraic theta null point. We also show how to algebraically compute Siegel modular forms of even weight given as polynomials in the theta constants by a careful choice of an affine lift of the theta null point. We then use these results to give an algebraic computation of Serre’s obstruction for principally polarized abelian threefolds isogenous to E³ and of the Igusa modular form in dimension 4. We illustrate our algorithms with examples of curves with many rational points over finite fields.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Anette Baumann / Alexander Jendorff / Frank Theisen (Hgg.), Religion – Migration – Integration. Studien zu Wechselwirkungen religiös motivierter Mobilität im vormodernen Europa, Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Hendrik Meyer-Magister, Wehrdienst und Verweigerung als komplementäres Handeln. Individualisierungsprozesse im bundesdeutschen Protestantismus der 1950er Jahre (RBRD 7), Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Jutta Stander-Dulisch, Glaubenskrisen, Neue Religionen und der Papst. Religion in „Stern“ und Spiegel“ von 1960 bis 2014, Bielefeld 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Analytical Bound State Solutions of the Klein-Fock-Gordon Equation for the Sum of Hulthén and Yukawa Potential within SUSY Quantum Mechanics - Ahmadov, A. I.; Aslanova, S. M.; Orujova, M. Sh.; Badalov, S. V. (Advances in High Energy Physics)
The relativistic wave equations determine the dynamics of quantum fields in the context of quantum field theory. One of the conventional tools for dealing with the relativistic bound state problem is the Klein-Fock-Gordon equation. In this work, using a developed scheme, we present how to surmount the centrifugal part and solve the modified Klein-Fock-Gordon equation for the linear combination of Hulthén and Yukawa potentials. In particular, we show that the relativistic energy eigenvalues and corresponding radial wave functions are obtained from supersymmetric quantum mechanics by applying the shape invariance concept. Here, both scalar potential conditions, which are whether equal and nonequal to vector potential, are considered in the calculation. The energy levels and corresponding normalized eigenfunctions are represented as a recursion relation regarding the Jacobi polynomials for arbitrary l states. Beyond that, a closed form of the normalization constant of the wave functions is found. Furthermore, we state that the energy eigenvalues are quite sensitive with potential parameters for the quantum states. The nonrelativistic and relativistic results obtained within SUSY QM overlap entirely with the results obtained by ordinary quantum mechanics, and it displays that the mathematical implementation of SUSY quantum mechanics is quite perfect.
Keywords: Nuclear and High Energy Physics

Towards a Trust-Aware Item Recommendation System on a Graph Autoencoder with Attention Mechanism - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Innovation Through Information Systems: Volume II: A Collection of Latest Research on Technology Issues)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

InP and AlInP(001)(2 × 4) Surface Oxidation from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Karmo, Marsel; Runge, Erich; Schmidt, Wolf Gero (ACS Omega)

Lattice parameters and electronic band gap of orthorhombic potassium sodium niobate K0.5Na0.5NbO3 from density-functional theory - Bidaraguppe Ramesh, Nithin; Schmidt, Falko; Schindlmayr, Arno (The European Physical Journal B)
We perform a theoretical analysis of the structural and electronic properties of sodium potassium niobate K1-xNaxNbO3 in the orthorhombic room-temperature phase, based on density-functional theory in combination with the supercell approach. Our results for x=0 and x=0.5 are in very good agreement with experimental measurements and establish that the lattice parameters decrease linearly with increasing Na contents, disproving earlier theoretical studies based on the virtual-crystal approximation that claimed a highly nonlinear behavior with a significant structural distortion and volume reduction in K0.5Na0.5NbO3 compared to both end members of the solid solution. Furthermore, we find that the electronic band gap varies very little between x=0 and x=0.5, reflecting the small changes in the lattice parameters.

Erratum: Efficient implementation of the GW approximation within the all-electron FLAPW method [Phys. Rev. B 81, 125102 (2010)] - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)

Bright correlated twin-beam generation and radiation shaping in high-gain parametric down-conversion with anisotropy - Riabinin, M.; Sharapova, Polina; Meier, Torsten (Optics Express)
Uniaxial anisotropy in nonlinear birefringent crystals limits the efficiency of nonlinear optical interactions and breaks the spatial symmetry of light generated in the parametric down-conversion (PDC) process. Therefore, this effect is usually undesirable and must be compensated for. However, high gain may be used to overcome the destructive role of anisotropy in order to generate bright two-mode correlated twin-beams. In this work, we provide a rigorous theoretical description of the spatial properties of bright squeezed light in the presence of strong anisotropy. We investigate a single crystal and a system of two crystals with an air gap (corresponding to a nonlinear SU(1,1) interferometer) and demonstrate the generation of bright correlated twin-beams in such configurations at high gain due to anisotropy. We explore the mode structure of the generated light and show how anisotropy, together with crystal spacing, can be used for radiation shaping.
Keywords: Atomic and Molecular Physics; and Optics

Transient subdiffusion via disordered quantum walks - Geraldi, Andrea; De, Syamsundar; Laneve, Alessandro; Barkhofen, Sonja; Sperling, Jan; Mataloni, Paolo; Silberhorn, Christine (Physical Review Research)

Statistical Benchmarking of Scalable Photonic Quantum Systems - Tiedau, J.; Engelkemeier, M.; Brecht, Benjamin; Sperling, Jan; Silberhorn, Christine (Physical Review Letters)

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Quantum Correlations beyond Entanglement and Discord - Köhnke, S.; Agudelo, E.; Schünemann, M.; Schlettwein, O.; Vogel, W.; Sperling, Jan; Hage, B. (Physical Review Letters)

Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Unraveling the electrochemical and spectroscopic properties of neutral and negatively charged perylene tetraethylesters - Wiebeler, Christian; Vollbrecht, Joachim; Neuba, Adam; Kitzerow, Heinz-Siegfried; Schumacher, Stefan (Scientific Reports)
Abstract A detailed investigation of the energy levels of perylene-3,4,9,10-tetracarboxylic tetraethylester as a representative compound for the whole family of perylene esters was performed. It was revealed via electrochemical measurements that one oxidation and two reductions take place. The bandgaps determined via the electrochemical approach are in good agreement with the optical bandgap obtained from the absorption spectra via a Tauc plot. In addition, absorption spectra in dependence of the electrochemical potential were the basis for extensive quantum-chemical calculations of the neutral, monoanionic, and dianionic molecules. For this purpose, calculations based on density functional theory were compared with post-Hartree–Fock methods and the CAM-B3LYP functional proved to be the most reliable choice for the calculation of absorption spectra. Furthermore, spectral features found experimentally could be reproduced with vibronic calculations and allowed to understand their origins. In particular, the two lowest energy absorption bands of the anion are not caused by absorption of two distinct electronic states, which might have been expected from vertical excitation calculations, but both states exhibit a strong vibronic progression resulting in contributions to both bands.
Keywords: Multidisciplinary

Atomically Thin Sheets of Lead‐Free 1D Hybrid Perovskites Feature Tunable White‐Light Emission from Self‐Trapped Excitons - Klement, Philip; Dehnhardt, Natalie; Dong, Chuan-Ding; Dobener, Florian; Bayliff, Samuel; Winkler, Julius; Hofmann, Detlev M.; Klar, Peter J.; Schumacher, Stefan; Chatterjee, Sangam; Heine, Johanna (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Controlled growth of ordered monolayers of N-heterocyclic carbenes on silicon - Franz, Martin; Chandola, Sandhya; Koy, Maximilian; Zielinski, Robert; Aldahhak, Hazem; Das, Mowpriya; Freitag, Matthias; Gerstmann, Uwe; Liebig, Denise; Hoffmann, Adrian Karl; Rosin, Maximilian; Schmidt, Wolf Gero; et al. (Nature Chemistry)

Polaronic enhancement of second-harmonic generation in lithium niobate - Kozub, Agnieszka L.; Schindlmayr, Arno; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)
Density-functional theory within a Berry-phase formulation of the dynamical polarization is used to determine the second-order susceptibility χ(2) of lithium niobate (LiNbO3). Defect trapped polarons and bipolarons are found to strongly enhance the nonlinear susceptibility of the material, in particular if localized at NbV–VLi defect pairs. This is essentially a consequence of the polaronic excitation resulting in relaxation-induced gap states. The occupation of these levels leads to strongly enhanced χ(2) coefficients and allows for the spatial and transient modification of the second-harmonic generation of macroscopic samples.

Theoretical analysis and simulations of two-dimensional Fourier transform spectroscopy performed on exciton-polaritons of a quantum-well microcavity system - Rose, Hendrik; Paul, Jagannath; Wahlstrand, Jared K.; Bristow, Alan D.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXV)

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, W.-R.; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (Journal of Physics Communications)

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, Wolf-Rüdiger; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Process-reliable Injection Molding of Highly Filled Wood-Plastic-Composites (WPC) - Moritzer, Elmar; Flachmann, Felix (PPS-36 Proceedings)

Mediating close friendship intimacy in times of (social) distance - Teichert, Jeannine (Networking Knowledge)

Modeling and improvement of a packed bed latent heat storage filled with non-spherical encapsulated PCM-Elements - Grabo, Matti; Acar, Emre; Kenig, Eugeny (Renewable Energy)

Cutting Blades for Food Processing Applications Manufactured Using Innovative Spin Forming - Rostek, Tim; Makeieva, Hanna; Homberg, Werner (Proceedings of the 13th International Conference on the Technology of Plasticity)

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Investigation of the influence of varying tumbling strategies on a tumbling self-piercing riveting process - Wituschek, Simon; Kappe, Fabian; Lechner, Michael (Production Engineering)

Investigations and Improvements in 3D-DIC Optical Residual Stress Analysis—A New Temperature Compensation Method - Dahms, Frederik; Homberg, Werner (Forming the Future)

Determining the heat flow through the cabinet walls of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al. (International Journal of Refrigeration)
The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary be- cause current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measure- ment method is developed to determine the k ·A value over time. With this method, the k ·A value of four household refrigerating appliances was determined over an interval of 14 months. The k ·A value increased between 3.6% and 11.5% during this period.

Investigating the real life energy consumption of refrigeration appliances in Germany: Are present policies sufficient? - Hueppe, Christian; Geppert, Jasmin; Moenninghoff-Juessen, Julia; Wolff, Lena; Stamminger, Rainer; Paul, Andreas; Elsner, Andreas; Vrabec, Jadran; Wagner, Hendrik; Hoelscher, Heike; Becker, Wolfgang; Gries, Ulrich; et al. (Energy Policy)
Domestic refrigeration appliances are standard household commodities. Although policies, such as the energy labelling, prompted technical improvements and decreased appliance energy consumption throughout recent decades, important parameters were disregarded. These refer to the efficiency loss over time and the consumer behaviour. The objective of this contribution was to develop a dynamic energy model to determine the power consumption of refrigeration appliances considering degradation factors and behaviour. These were included by model parameters for direct consumer interactions, such as the storage behaviour, door openings and temperature setting, as well as indirect actions, e.g. exposing an appliance to specific temperature conditions at an installation site. For this, an online-survey was conducted to evaluate the consumer behaviour. A total of 706 consumers participated in the national questionnaire, serving as input for the dynamic energy model. It was found that the efficiency loss increases the power consumption by at least 1% annually, leading to an excess of 10% after 10 years of usage. Another important finding was that 32.5% of appliance’s power consumption results from consumer behaviour, whereas the promotion of behavioural changes leads to a significant decrease of the consumer-induced consumption. Consequently, this study provides a tool to evaluate the impact of policies targeting refrigeration appliances, stressing that efficiency loss and behaviour should be integrated into future policy approaches.

Crossraods of Collective Memory. Canadian Memoir at the Junction of lieux and nœuds de mémoire. - Jende, Yvonne Kristin (The Place of Memory and the Memory of Place, International Conference)

Truth Be Told, ... or Not? Reality and Perspective in New Sincerity Memoir. - Jende, Yvonne Kristin (Bridges and Barriers: Perspectives of Progress and Preservation, Interdisciplinary and International Conference)

Online State Estimation for Microscopic Traffic Simulations using Multiple Data Sources* - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (VEHITS 2021 Proceedings of the 7th International Conference on Vehicle Technology and Intelligent Transport Systems)
The online fitting of a microscopic traffic simulation model to reconstruct the current state of a real traffic area can be challenging depending on the provided data. This paper presents a novel method based on limited data from sensors positioned at specific locations and guarantees a general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. In these considerations, the actual purpose of research is of particular importance. Here, the research aims at improving the traffic flow by controlling the Traffic Light Systems (TLS) of the examined area which is why the current traffic state and the route choices of individual road users are the matter of interest. An integer optimization problem is derived to fit the current simulation to the latest field measurements. The concept can be transferred to any road traffic network and results in an observation of the current multimodal traffic state matching at the given sensor position. First case studies show promosing results in terms of deviations between reality and simulation.
Keywords: Microscopic Traffic Simulation; Online State Estimation; Mixed Road Users; Sensor Fusion; Integer Programming; Route Choice; Vehicle2Infrastructure

Combining Mobility, Heterogeneity, and Leasing Approaches for Online Resource Allocation - Berger, Thilo Frederik

Online k-Facility Reallocation using k-Server Algorithms - Pranger, Sebastian